The Relationship between Household Environmental Health and the Incidence of Pulmonary Tuberculosis Community Health Center in Jambi City - Nada Zahra, Risa; Aurora, Wahyu Indah Dewi; Harahap, Huntari (Scientific Of Environmental Health and Diseases, 2025)
Background: Pulmonary tuberculosis is a preventable infectious disease, but according to 2022 data, pulmonary TB ranks second in causing deaths worldwide after the coronavirus (COVID-19). Household environmental conditions are thought to play a role in its transmission. This study aims to determine the relationship between lighting, humidity, and ventilation in homes and the incidence of pulmonary TB at the Pakuan Baru Community Health Center, Simpang Kawat Community Health Center, and Paal X Community Health Center in 2024. Method: This research uses a case-control design with a sample of 104 respondents (26 cases, 78 controls) in three community health center areas. Lighting and humidity measurements were taken using a lux meter and hygrometer, while windows were measured using observation sheets. Data were analyzed univariately and bivariately using the Chi-Square test with Odds Ratio (OR). Results: Most homes of TB patients have inadequate environmental conditions. Analysis shows a significant relationship between inadequate humidity (OR=54.86; 95% CI:11.60-259.52; p<0.001), inadequate lighting (OR=13.83; 95% CI: 4.61-41.52; p<0.001), and lack of windows (OR=4.29; 95% CI: 1.62-11.35; p=0.002) with TB incidence. Conclusion: Poor household environmental conditions, such as humidity, lighting, and window conditions, are risk factors for TB. It is recommended that TB prevention programs integrate the promotion of household environmental improvements.